Effects of Previous Kasai Surgery on Gut Microbiota and Bile Acid in Biliary Atresia With End-Stage Liver Disease - Song, Wei; Sun, Li-Ying; Zhu, Zhi-Jun (Frontiers in Medicine, 2021)
Background & Aims: Biliary atresia (BA) is the most common cholestatic liver disease in neonates. Although the Kasai procedure can improve temporary biliary drainage in some cases, complications and liver fibrosis still develop. Liver transplantation is the ultimate treatment. The current study aimed to investigate the effect of previous Kasai surgery on gut microbiota and bile acid in BA with end-stage liver disease. Methods: Patients with BA with end-stage liver disease were divided into two groups according to whether they had previously undergone Kasai surgery (non-Kasai: n=8, post-Kasai: n=8). Metagenomic sequencing and ultraperformance liquid chromatography/tandem mass spectrometry were performed to identify the gut microbiota and bile acid. Results: Previous Kasai surgery had some effects on gut microbiota and bile acid in BA with end-stage liver disease. In the gut microbiome, the differential species were mainly distributed at the species level. Veillonella atypica had a significant increase in the non-Kasai group (P < 0.05). Bacteroides spp., Prevotella spp., Barnesiella spp., Parabacteroides spp., Heliobacterium spp., Erysipelatoclostridium spp. and Diaporthe spp. were increased in the post-Kasai group (P < 0.05). Concerning functional profiles, methionine biosynthesis was enriched in the non-Kasai group, while pyridoxal biosynthesis and riboflavin biosynthesis were enriched in the post-Kasai group (linear discriminant analysis > 2, P < 0.05). In stools, 17 bile acids were distinctly elevated in the post-Kasai group, such as cholic acid, chenodeoxycholic acid, β-muricholic acid and tauro α-muricholate (P < 0.05). Spearman correlation test showed that V. atypica had an enormously positive correlation with liver enzymes. Faecalibacterium prausnitzii and Escherichia coli were associated with derivatives of the alternative pathway of bile acid metabolism. Conclusion: Previous Kasai surgery can improve the gut microbiota and bile acid in patients with BA with end-stage liver disease. This improvement contributes to maintaining the intestinal barrier.